A comprehensive comparison of the in vitro hemocompatibility of extracorporeal centrifugal blood pumps - Li, Ping; Mei, Xu; Ge, Wanning; Wu, Tingting; Zhong, Min; Huan, Nana; Jiang, Qiubo; Hsu, Po-Lin; Steinseifer, Ulrich; Dong, Nianguo; Zhang, Liudi (Frontiers in Physiology, 2023)
Purpose: Blood damage has been associated with patients under temporary continuous-flow mechanical circulatory support. To evaluate side effects caused by transit blood pumping, in vitro hemocompatibility testing for blood damage in pumps is considered a necessary reference before clinical trials. Methods: The hemocompatibility of five extracorporeal centrifugal blood pumps was investigated comprehensively, including four commercial pumps (the Abbott CentriMag, the Terumo Capiox, the Medos DP3, and the Medtronic BPX-80) and a pump in development (the magAssist MoyoAssist®). In vitro hemolysis was tested with heparinized porcine blood at nominal operating condition (5 L/min, 160 mmHg) and extreme operating condition (1 L/min, 290 mmHg) by a circulation flow loop. Hematology analysis concerning the blood cell counts and the degradation of high molecular weight von Willebrand factor (VWF) during 6-hour circulation were also evaluated. Results: Comparing the in vitro hemocompatibility of blood pumps at different operations, the blood damage was significantly more severe at extreme operating condition than that of nominal operating condition. The performance of five blood pumps was arranged in different order at these two operating conditions. The results also demonstrated superior hemocompatibility of CentriMag and MoyoAssist® at two operating conditions, with overall low blood damage at hemolysis level, blood cell counts, and degradation of high molecular weight VWF. It suggested that magnetic bearings have advantage in hemocompatibility compared to mechanical bearing of blood pumps. Conclusion: Involving multiple operating conditions of blood pumps in in vitro hemocompatibility evaluation will be helpful for clinical application. Besides, the magnetically levitated centrifugal blood pump MoyoAssist® has great potential in the future, as it demonstrated good in vitro hemocompatibility.